A Rare Coexistence of Thyrotoxic Cardiomyopathy and Asthma in Graves’ Disease: Clinical Challenges and Management Strategies: A Case Report - Mutiara Lirendra; Eva Niamuzisilawati; Ega Caesaria; Brilliant Van Fitof; A Farih Raharjo; Adi Bestara (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
Graves' disease is the most common autoimmune hyperthyroid disorder. Thyrotoxic cardiomyopathy (TCM) is a rare but potentially lethal complication of thyrotoxicosis, with an incidence of <1%. Betablocker is one of the drugs of choice in treating TCM. However, in asthma patient, beta-blocker may induce bronchoconstriction. We report a rare case of a 36-year-old male presented with complaints of shortness of breath, wheezing, cough, and palpitation. The patient had a history of asthma. Physical examination revealed diffuse thyroid enlargement, exophthalmos, tremor, cardiomegaly, irregular heart sounds, rales, wheezing in both lungs, and BMI was underweight. Wayne index was 20 (hyperthyroid) and Burch Wartofsky score was 35 (impending storm). Laboratory results showed low Thyroid-stimulating hormone level and high level of Free-T3, Free-T4, Thyroid-Stimulating Hormone Receptor Antibodies, and N-terminal pro-B-type natriuretic peptide. Chest X-ray showed cardiomegaly. electrocardiogram showed atrial fibrillation RVR. Echocardiography showed segmental wall motion abnormality EF 48%. Patient was diagnosed with Graves’ disease with hyperthyroidism, acute asthma exacerbation, Heart failure with mildly reduced ejection fraction NYHA III due to thyrotoxic cardiomyopathy. Patient was treated with methimazole, shortacting beta-agonists, corticosteroid, digitalis, diuretics, anticoagulant, and angiotensin receptor blockers. During follow up, laboratory results, ECG, and clinical symptoms were improved. The management of Graves' disease with hyperthyroidism and TCM focuses primarily on controlling the thyroid hormone levels to prevent further cardiac deterioration. The complex interplay between managing thyroid hormone levels and preventing asthma exacerbation in this patient highlights the need for a multidisciplinary approach to optimize treatment outcomes. Graves' hyperthyroid patients with cardiomyopathy and asthma require holistic, comprehensive, and meticulous drug selection to prevent exacerbation.